Study of the aqueous extract impact of Vitex agnus castus on the female reproductive system hormones of the Albino Rabbit exposed to oxidative stress - Munif Sa'ab Al-Janaby; Mousa Jasim Al-Humesh; Bassam Dheyaa Al-Samarray (Tikrit Journal of Pure Science, 2023)
In view of the wide use of the Vitex agnus castus in treatment of the monstrous troubles and as a regulation of the sexual Hormones, this study was conducted to know the impact of the aqueous extract of the Vitex agnus castus compared with Vitamin E on the sexual Hormones in the female white rabbits exposed to the hydrogen peroxide (0.5%) for (30) days and the rabbit were (6-8) months old and their weights (1300-1700) g. They were divided at random into (10) groups, each (5) rabbits to one group as following: (1) The health control group consumed the normal drinking water and the standard nutrition, (2) the infected control group consumed the hydrogen peroxide with drinking water and a nutrient, (3) the extract had a concentration (50mg/kg), (4) the extract(50mg/kg)+H2O2, (5) the extract (50mg/kg)+Vitamin E, (6) the extract (50mg/kg)+Vitamin E+H2O2, (7) Vitamin E, (8) the extract (100mg/kg), (9) the extract (100mg/kg)+H2O2, (10) the extract (100mg/kg)+Vitamin E+H2O2. The concentration of the sexual Hormones were estimated to know the impact of the aqueous extract of Vitex agnus castus on the functions and capacity of the sexual organ in the female rabbits. The results of study showed that giving these rabbits H2O2 with drinking water led to decrease significantly in concentrations of Progesterone, Estrogen, FSH, LH, Hormones, whereas they showed a significant increase in concentration of prolactin Hormone compared with the healthy control group. It was also showed a significant increase in Progesterone Hormone at the dose(50mg/kg) with Vitamin E compared with the healthy control group, as well as there was a significant decrease in concentration of LH Hormone in all groups compared with the healthy control except the Vitamin E group only that showed a significant increase(P<0.01), whereas the concentration of Prolactin Hormone decreased in all groups compared with the healthy and infected. So we conducted that the Vitex agnus castus had an important role in fertility and inhibition of the Prolactin Hormone as the main cause of injuring the women  by infertility.